Strategi Pengembangan Kedai Kopi Sanggabuana pada BUMDes Buana Mekar di Kecamatan Tegalwaru Kabupaten Karawang - Safya, Thasya Nanda; Muharam, Muharam; Yusiana, Ekalia (Universitas Galuh, 2024)
Sanggabuana coffee shop is a business established by BUMDes Buana Mekar in Mekarbuana Village, Tegalwaru District, Karawang Regency. Sanggabuana coffee shop has the main problem of turnover instability caused by the lack of visitors. This coffee shop has many internal and external constraints, but has the potential to be developed. The purpose of this research is to identify the main factors (strengths, weaknesses, opportunities and threats), formulate alternative strategies, and determine strategy priorities. This research is a qualitative and quantitative research using purposive sampling technique. The data used are primary and secondary data. Primary data was obtained from interviews and filling out questionnaires by 16 respondents (coffee shop Chief, Chairman and Treasurer of BUMDes, Head of Mekarbuana Village, coffee shop employees and consumers). Secondary data was obtained from the Central Bureau of Statistics and the Mekarbuana Village Government. The data analysis techniques used are the IFE matrix, EFE matrix, SWOT matrix, and QSPM matrix. The results of the analysis show that the main strength is the product comes from quality organic coffee beans and friendly service to consumers (0.25), the main weakness is the menu is not yet varied and there is no companion menu and poor data and financial management (0.09), the main opportunity is become karawang specialty products (0.30), and the main threat is competitors offer a more varied menu and attractive place (0.26). There are 9 alternative strategies and the priority strategies that can be implemented are developing a more contemporary coffee shop concept and adding signage with a score of 6.04.